2013
DOI: 10.1111/ijs.12071
|View full text |Cite
|
Sign up to set email alerts
|

Stroke and Cancer: Misfortunes Never Come Singularly

Abstract: Cancer patients exhibit an elevated stroke risk (1)(2)(3)(4)(5). In a case-control study examining the epidemiology of cancer in stroke patients and their clinical course, we identified 72 active cancer and 72 control patients from the 1493 stroke admissions to Princess Margaret Hospital, Hong Kong in 2009. The prevalence of cancer among stroke patients was 4·8% (Table 1), and stroke was the first symptom of their cancer in nine patients. The proportions of ischemic stroke (IS) (79·2%) and haemorrhagic stroke … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
2
7
0
Order By: Relevance
“…Previous studies have reported that the cryptogenic stroke rate in cancer patients is relatively high; however, there has been no study of the cryptogenic stroke rate according to the presence of active cancer within the same study population. It has been suggested that paroxysmal atrial fibrillation is the latent common cause of cryptogenic stroke in the general population .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous studies have reported that the cryptogenic stroke rate in cancer patients is relatively high; however, there has been no study of the cryptogenic stroke rate according to the presence of active cancer within the same study population. It has been suggested that paroxysmal atrial fibrillation is the latent common cause of cryptogenic stroke in the general population .…”
Section: Discussionmentioning
confidence: 90%
“…However, these stroke mechanisms are often difficult to diagnose except in an autopsy; as a result, they can be diagnosed as cryptogenic stroke in clinical practice. In fact, in patients with cancer, the incidence of cryptogenic stroke is reported to account for approximately 40–50% of stroke mechanisms and is more prevalent in patients without cancer . Previous studies have demonstrated that cancer patients with cryptogenic stroke often have high plasma D‐dimer levels and multiple vascular lesion patterns and are associated with reduced survival, suggesting that cryptogenic stroke in these patients needs specific consideration.…”
Section: Introductionmentioning
confidence: 99%
“…13, 14 In a case-control study, 32% of cancer patients with ischemic stroke had in-hospital death versus 13% of non-cancer patients with ischemic stroke. 37 Small retrospective studies have reported that high D-dimer levels may be predictive of early neurological deterioration and death in cancer-associated stroke. 15, 38 However, the prognostic utility of D-dimer and other biomarkers in cancer-associated stroke requires confirmation in prospective studies with systematic assessments.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Among ischemic stroke patients, comorbid cancer is associated with increased stroke severity, early neurological deterioration, and in‐hospital death . Median survival was 84 days in 263 patients with active solid or hematological cancer diagnosed with acute ischemic stroke at a quaternary‐care cancer center .…”
Section: Prognosismentioning
confidence: 99%
“…Stroke patients with Alessia Hug and SungJu Weber these authors contributed equally to this work. cancer had higher in-hospital mortality [15][16][17][18], however, the availability of longitudinal data is limited.…”
Section: Introductionmentioning
confidence: 99%